1998
DOI: 10.1021/jf980456o
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Thermal Characterization of Peroxidase from Okra (Hibiscus esculentum)

Abstract: Thermal characteristics and substrate specificity of peroxidase (POX) from okra were determined. Crude POX was separated into eight fractions (P1-P8) by DEAE-cellulose chromatography. Heat inactivation of POX was biphasic and fitted to a first-order kinetic model. Inactivation rates of crude POX and eight POX fractions at 70°C varied between (63.499 and 123.809) × 10 -2 min -1 for the heat-labile fractions and (11.255 and 31.441) × 10 -2 min -1 for the heat-stable fractions. Activation energies for the inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Purified peroxidases have been obtained from diverse plant sources (Deepa, Arumughan 2002), such as spring cabbage, soy bean and rice leaves (Ito et al 1991), tea (Kvaratskhelia et al 1997), okra (Yemenicioglu et al 1998), Ipomoea palmetto (Srinivas et al 1999) and Copaifera longsdorffi (Maciel et al 2007). However, less attention has been directed toward sources that are naturally widely available and regarded as unwanted in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Purified peroxidases have been obtained from diverse plant sources (Deepa, Arumughan 2002), such as spring cabbage, soy bean and rice leaves (Ito et al 1991), tea (Kvaratskhelia et al 1997), okra (Yemenicioglu et al 1998), Ipomoea palmetto (Srinivas et al 1999) and Copaifera longsdorffi (Maciel et al 2007). However, less attention has been directed toward sources that are naturally widely available and regarded as unwanted in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that mPOD‐I had undergone thermal inactivation at 70C with an inactivation rate constant ( k ) of 72.9 × 10 −3 /min compared with that of mPOD‐II with k value at 97.9 × 10 −3 /min. Isoenzymes with different thermal inactivation rate constant were also reported for okra mPOD isoenzymes, where at 70C, the heat labile isoenzyme showed k value at 63.5 × 10 −3 /min and the heat‐stable isoenzyme with k value of 11.26 × 10 −3 /min (Yemenicioglu et al . 1998a).…”
Section: Resultsmentioning
confidence: 89%
“…Adams (1991) added that this complex could be a carbohydrate, which is known to form a complex with POD molecules. However, Yemenicioglu et al . (1998) reported an exceptionally higher stability for the purified pinto beans mPODs with an inactivation rate ( k ) value at 70C of 24.0 × 10 −3 /min and 32.8 × 10 −3 /min, respectively, for the thermal stable fraction 1 and fraction 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxidase (POD) an oxidoreductase is a heme protein, catalyses the oxidation of a wide variety of organic and inorganic substrates using hydrogen peroxide as the electron acceptor (1). Peroxidases are widely distributed in living organisms including microorganisms, plants and animals (2).…”
Section: Introduction:-mentioning
confidence: 99%